2009
DOI: 10.1097/gim.0b013e3181b6573d
|View full text |Cite
|
Sign up to set email alerts
|

A gene dosage map of Chromosome 18: A map with clinical utility

Abstract: Purpose: Microarray technology has revolutionized the field of clinical genetics with the ability to detect very small copy number changes. However, challenges remain in linking genotype with phenotype. Our goal is to enable a clinical geneticist to align the molecular karyotype information from an individual patient with the annotated genomic content, so as to provide a clinical prognosis. Methods: We have combined data regarding copy number variations, microdeletion syndromes, and classical chromosome abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…It has been reported that chromosomes 17 and 18 contained many disease-associated genes [32-37]. The present study initially demonstrated TCs-specific genes, of which 16 and 10 up-regulated and 68 and 22 down-regulated, in chromosomes 17 and 18, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…It has been reported that chromosomes 17 and 18 contained many disease-associated genes [32-37]. The present study initially demonstrated TCs-specific genes, of which 16 and 10 up-regulated and 68 and 22 down-regulated, in chromosomes 17 and 18, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…In our first effort to do this for chromosome 18, we found dosage information on 86 of the 253 known genes on chromosome 18 [Cody et al, 2009]. Therefore, one-third of genes could be provisionally assigned a dosage category using existing information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, critical regions for the phenotypes associated with numerous chromosome abnormalities have been identified. A selected list is as follows: 1p36 [Redon et al, 2005]; 4p [Maas et al, 2008]; 5p [Zhang et al, 2005]; 9p [Barbaro et al, 2009]; 11q [Coldren et al, 2008]; 13q [Kirchhoff et al, 2009]; 18q [Cody et al, 2009]; and 21 [Korbel et al, 2009]. Although these types of data identify regions and rarely identify singles genes, these data are never-the-less an important resource for information about potential annotation of specific genes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By following the directions in the section of the management guides labeled, “How to create a personalized syndrome description,” the exact base pair coordinates of the copy number change can be used to create a map view of the dosage sensitive genes and the phenotypes known to be associated with that region of the chromosome (Cody et al, ). In the case of 18p‐ used as an illustration here, the patient has a 3 Mb terminal deletion of 18p.…”
Section: Introductionmentioning
confidence: 99%